2002
DOI: 10.1002/icd.251
|View full text |Cite
|
Sign up to set email alerts
|

The developmental change in strategies parents employ to settle young children to sleep, and their relationship to infant sleeping problems, as assessed by a new questionnaire: the Parental Interactive Bedtime Behaviour Scale

Abstract: The development of a new parental self-report questionnaire, the Parental Interactive Bedtime Behaviour Scale (PIBBS) is described. The PIBBS was designed to capture a wide range of parental behaviours used to settle infants off to sleep. The commonest behaviours employed were giving a feed, talking softly to the child, cuddling in the arms, and stroking. A factor analysis revealed five settling strategies; 'active physical comforting' (e.g. cuddling in arms); 'encouraging infant autonomy' (e.g. leaving to cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
3
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 21 publications
16
107
3
4
Order By: Relevance
“…Infants who fall asleep alone in the crib and sleep in a crib in a separate room are more likely to sleep through the night, with fewer night wakings. 9,55,56 It is also possible that parents of such infants are less likely to notice when their infant wakes up, because of the distance and visual separation.…”
Section: Discussionmentioning
confidence: 99%
“…Infants who fall asleep alone in the crib and sleep in a crib in a separate room are more likely to sleep through the night, with fewer night wakings. 9,55,56 It is also possible that parents of such infants are less likely to notice when their infant wakes up, because of the distance and visual separation.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores indicated more active comforting. Settling in the parents' bed has been significantly correlated with infants' sleeping problems (Morrell & Cortina-Borja, 2002). In the present study, Cronbach's alpha for the subscale was .75.…”
Section: Mothers' Bedtime Behavior To Settle Infantsmentioning
confidence: 99%
“…To date, maternal psychopathology received great attention (anxiety and depression) (Keller, Buckhalt, and El-Sheikh, 2008): the authors reported that children's sleep difficulties are related to psychological distress in mothers (Martin et al, 2007) and they are connected with an increase of marital conflict (Kelly and El-Sheikh, 2011) and of parenting stress (Morrell and Cortina-Borja, 2002).…”
Section: Introductionmentioning
confidence: 99%